A New Dimeric Copper(II) Complex of Hexyl Bis(pyrazolyl)acetate Ligand as an Efficient Catalyst for Allylic Oxidations - Luca Bagnarelli; Alessandro Dolmella; Carlo Santini; Riccardo Vallesi; Roberto Giacomantonio; Serena Gabrielli; Maura Pellei (Molecules, 2021)
A new dimeric copper(II) bromide complex, [Cu(LOHex)Br(μ-Br)]2 (1), was prepared by a reaction of CuBr2 with the hexyl bis(pyrazol-1-yl)acetate ligand (LOHex) in acetonitrile solution and fully characterized in the solid state and in solution. The crystal structure of 1 was also determined: the complex is interlinked by two bridging bromide ligands and possesses terminal bromide ligands on each copper atom. The two pyrazolyl ligands in 1 coordinate with the nitrogen atoms to complete the Cu coordination sphere, resulting in a five-coordinated geometry—away from idealized trigonal bipyramidal and square pyramidal geometries—which can better be described as distorted square pyramidal, as measured by the τ and χ structural parameters. The pendant hexyloxy chain is disordered over two arrangements, with final site occupancies refined to 0.705 and 0.295. The newly synthesized complex was evaluated as a catalyst in copper-catalyzed C–H oxidation for allylic functionalization through a Kharasch–Sosnovsky reaction without any external reducing agent. Using 0.5 mol% of this catalyst, and tert-butyl peroxybenzoate (Luperox) as an oxidant, allylic benzoates were obtained with up to 90% yield. The general reaction time was only slightly decreased to 24 h but a very significant decrease in the alkene:Luperox ratio to 3:1 was achieved. These factors show relevant improvements with respect to classical Kharasch–Sosnovsky reactions in terms of rate and amount of reagents. The present study highlights the potential of copper(II) complexes containing functionalized bis(pyrazol-1-yl)acetate ligands as efficient catalysts for allylic oxidations.